Biomechanical report for the IAAF World Championships London 2017 long jump women's - Tucker, C.; Nicholson, G.; Cooke, M.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The women`s long jump final took place on the night of August 11th. Coming into the final, Brittney Reese of the USA was favourite given she had performed a world leading jump of 7.13 metres earlier in the year. Tianna Bartoletta was also a strong contender as she was the Olympic Champion from the previous year. It was an exciting final where Reese clinched the gold medal with the better of her two scoring efforts measured at 7.02 metres. Darya Klishina produced four successive season`s bests with her best effort being 7 metres exactly. Bartoletta, despite being a strong contender, had to settle for the bronze medal but she only secured this with her final attempt of 6.97 metres. This attempt beat Ivana Španovic, an early leader, by just one centimetre. (Attention! registration on the IAAF site is required for downloading)